Intellectual property and intelligence with Learning result of educational languages of islamic Education (pai) learners in smkn 4 padang - Diones Aliaski (Fakultas Sastra Universitas Ekasakti, 2018)
The purpose of this study is to know: 1) The relationship of intellectual intelligence with learning outcomes of learners in SMKN 4 Padang. 2) Relationship of emotional intelligence with learning outcomes of learners in SMKN 4 Padang. 3) The relationship of intellectual intelligence and emotional intelligence together with the learning outcomes of learners in SMKN 4 Padang. This research is a type of field research (field research). The nature of this studyis quantitative. Variables are everything that willbe the object of research observation. Population is the amount that is on the object or subject studied that includes all the characteristics or properties possessed by the object or subject it. The population in this study were students of class XI SMKN 4 Padang Year Teaching 2015/2016 which amounted to 457 people. The sample is